Implementing a SAK EMKM-Based Accounting Information System in a Micro and Small Enterprise in the Bakery Sector - Fajriani Azis; Adriansyah Adriansyah; Dwi Ayu Siti Hartinah; Rafiqa Hastharita (PT. Global Research Collaboration, 2025)
The advancement of information technology offers significant opportunities for Micro and Small Enterprises (MSEs) to enhance business management through the adoption of structured Accounting Information Systems (AIS). However, many MSEs continue to face challenges in preparing financial statements that comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This community assistance initiative aims to support a bakery-sector MSE in implementing a SAK EMKM-based AIS to improve financial transparency, accountability, and reporting accuracy. The assistance was delivered through field observations, interviews, and hands-on training sessions with the business owner and employees focusing on the accounting cycle and recording techniques. The results indicate that the adoption of a more structured accounting system enabled the MSE to prepare monthly income statements, equity reports, and statements of financial position more systematically. The program also enhanced the entrepreneur’s financial literacy and supported more informed decision-making. These findings demonstrate that implementing a SAK EMKM-based AIS is effective in strengthening financial governance and promoting business sustainability for MSEs.